2009
DOI: 10.1074/jbc.m806759200
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum/Golgi Nucleotide Sugar Transporters Contribute to the Cellular Release of UDP-sugar Signaling Molecules

Abstract: Extracellular UDP-sugars promote cellular responses by interacting with widely distributed P2Y 14 receptors, but the mechanisms by which these molecules are released from cells are poorly understood. Given the active role of UDP-sugars in glycosylation reactions within the secretory pathway, we hypothesized that UDP-sugar release includes an exocytotic component. This hypothesis was tested by assessing the contribution of endoplasmic reticulum (ER)/Golgi-resident UDPGlcNAc transporters to the cellular release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 59 publications
4
71
0
Order By: Relevance
“…Previous studies indicated robust levels of UDP-sugars in in vivo airway surface liquid (BALF) from chronically diseased lungs (e.g., cystic fibrosis) [24], but the extent to which concentrations of UDP-sugars in CF airway secretions differ from healthy controls is not known. Therefore, we examined the nucleotide content in sputum samples (believed to reflect secretions from the large airways) [38] obtained from CF patients with moderate or severe lung disease and from healthy control subjects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies indicated robust levels of UDP-sugars in in vivo airway surface liquid (BALF) from chronically diseased lungs (e.g., cystic fibrosis) [24], but the extent to which concentrations of UDP-sugars in CF airway secretions differ from healthy controls is not known. Therefore, we examined the nucleotide content in sputum samples (believed to reflect secretions from the large airways) [38] obtained from CF patients with moderate or severe lung disease and from healthy control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that UDP-N-acetylglucosamine is present in BALF isolated from patients with CF and other inflammatory diseases at concentrations similar to UDPglucose concentrations [24]. On a speculative basis, UDP-Nacetylglucosamine and potentially UDP-galactose and UDPglucuronic acid may contribute to P2Y 14 R-dependent lung phenotypes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations